PENGARUH ENDORSEMENT INFLUENCER DALAM MEMBENTUK KEPERCAYAAN KONSUMEN TERHADAP BRAND YU MARNI - Nopita, Dewi; Rodhiyah Mardhiyyah; Echa Yulia Checar; Dwi Indah Lestari (Politeknik Ubaya, 2024)
Consumer trust is a key factor in purchasing decisions. Influencer endorsements have become an increasingly popular marketing strategy in efforts to influence consumer preferences. Influencer s possess a level of credibility that impacts the trust levels towards the Yu Marni brand. Yu Marni is a business that sells products made from corn and cassava, yet its product marketing has not been optimal, failing to reach the sales target. Therefore, utilizing Influencer s and leveraging their credibility in advertising campaigns is crucial. However, Yu Marni is challenged to build brand trust to compete with other brands. The objective of this research is to determine the extent of the influence of Influencer endorsements in shaping consumer trust in the Yu Marni brand. The research method includes interviews and surveys conducted through questionnaires. The questionnaires were created using Google Forms and shared via WhatsApp groups. 31 respondents filled out the questionnaires. The research results prove that Influencer endorsements significantly influence consumer trust in the Yu Marni product. The study has demonstrated that consumers agree that Influencer s have successfully introduced Yu Marni products, as evidenced by a 78.3% response rate. Additionally, 56.5% of respondents felt inspired to purchase Yu Marni products after seeing promotions by Influencer s. Influencer endorsements have a significant positive impact on building consumer trust in the Yu Marni brand.